Antithrombotic therapy after transcatheter aortic valve replacement: current perspective. (March 2021) - Eckstein, Janine; Liu, Shuangbo; Toleva, Olga; Yanagawa, Bobby; Verma, Subodh; Cheema, Asim N.
Abstract : Purpose of review: Transcatheter aortic valve replacement (TAVR) has expanded as a treatment option for severe aortic stenosis throughout the surgical risk spectrum. Decreasing procedural risk and inclusion of lower risk population has shifted the focus to optimization of postprocedural management and balancing the thrombotic and bleeding complications. In this review, we outline various patient and procedure related factors affecting choice of antithrombotic therapy post TAVR and provide an update of recent development in this area. Recent findings: Multiple studies have confirmed the high incidence of both ischemic and bleeding complications in the early to midterm post-TAVR. In addition, new data has emerged for the role of high resolution computed tomography to detect decreased leaflet mobility and leaflet micro thrombi associated with implications for bioprosthetic valve dysfunction and cerebrovascular events post TAVR. Randomized clinical trials have reported increased bleeding with dual antiplatelet therapy (DAPT) and oral anticoagulation (OAC) plus antiplatelet therapy. These findings suggest that aspirin monotherapy or OAC monotherapy likely provides the appropriate balance for antithrombotic protection and risk of bleeding. Summary: Majority of patients undergoing TAVR have multiple comorbidities and are at increased risk of ischemic and bleeding complications. In the absence of robust clinical evidence, there is significant variability among guideline recommendations and antithrombotic therapy post TAVR across institutions. The available evidence confirms a high rate of bleeding with more potent and prolonged antithrombotic regimens without a documented benefit for clinical endpoints. The authors favor a conservative anti thrombotic approach and suggest monotherapy with aspirin or systemic anticoagulation based upon an individual's risk of thromboembolic complications. DAPT is reserved for patients with recent stenting and OAC plus aspirin is prescribed for patients with established CAD in the post TAVR setting.